A feedback model to predict parameters for controlling the performance of a mechanical draft cooling tower. (25th July 2016) - Singh, Kuljeet; Das, Ranjan
Highlights: A feedback and control model for the forced draft cooling tower performance. Model simulation is presented for three different cases under varying heat load. Useful for solar cogeneration, ORC, diesel engine and HVAC applications. GA optimized results with feedback control save pump and blower power. Performance parameters also improve with feedback. Abstract: In this work, a feedback model has been proposed in order to control the performance of a mechanical draft cooling tower under varying heat load conditions suiting diverse applications such as solar power generation, HVAC and diesel engine. The model uses specific objective functions to meet the operating conditions related with the process requirement under varying heat load. These objective functions have been formulated using empirical correlations corresponding to different performance parameters developed from experimental data. Thereafter, an inverse method-based feedback model is made to control the cooling tower's performance for different outputs. The simulated model considers different cases closely relating to practical use of the cooling tower. Further, by monitoring the inlet water temperature with time, the controlling variable governed by water to air ratio has been adjusted to optimize the tower operation. It is concluded that for different situations, the proposed inverse feedback model is an optimized tool to control the tower performance.